3D TiC/C Core/Shell Nanowire Skeleton for Dendrite‐Free and Long‐Life Lithium Metal Anode. Issue 8 (4th December 2017) - Liu, Sufu; Xia, Xinhui; Zhong, Yu; Deng, Shengjue; Yao, Zhujun; Zhang, Liyuan; Cheng, Xin‐Bing; Wang, Xiuli; Zhang, Qiang; Tu, Jiangping
Abstract: Construction of stable dendrite‐free Li metal anode is crucial for the development of advanced Li–S and Li–air batteries. Herein, self‐supported TiC/C core/shell nanowire arrays as skeletons and confined hosts of molten Li forming integrated trilayer TiC/C/Li anode are described. The TiC/C core/shell nanowires with diameters of 400–500 nm exhibit merits of good lithiophilicity, high electrical conductivity, and abundant porosity. The as‐prepared TiC/C/Li anode exhibits prominent electrochemical performance with a small hysteresis of less than 85 mV beyond 200 cycles (3.0 mA cm −2 ) as well as a very high Coulombic efficiency up to 98.5% for 100 cycles at 1.0 mA cm −2 . When the structured anode is coupled with lithium iron phosphate or sulfur cathode, the assembled full cells with trilayer TiC/C/Li anodes display enhanced capability retention and improved Coulombic efficiency. This is ascribed to the unique TiC/C matrix, which can not only provide interspace for accommodating "hostless" Li, but also afford interconnected rapid transfer paths for electrons and ions with low local current densities, leading to effective inhabitation growth of Li dendrites and lower interfacial resistance. A fresh way for construction of advanced stable Li metal anodes is provided in this work. Abstract : A unique integrated trilayer TiC/C/Li anode is constructed through rational combination of self‐supported TiC/C core/shell nanowire arrays and melt‐infusion process. Attributed to ultralow current density, stabilized solid electrolyte interphase film, and limited volume change, the TiC/C/Li anode exhibits lower hysteresis, enhanced cycling stability, and higher Coulombic efficiency.